Eating at school: on children, biopower and care in Turin, Italy. Issue 4 (4th July 2022) - Toldo, Alessia
ABSTRACT: Food concerns practices with material and discursive effects on bodies, involving, at the same time, relations of power and care. The international debate has widely analysed food in terms of biopolitical technologies and ethics of care, paying particular attention to school meals. In particular, school canteens constitute physical and relational contested spaces, characterized by different rationalities and perspectives. Drawing from qualitative research carried out in Turin, Italy, this paper unpacks school food discourses and practices by analysing the coexistence and entanglements of biopower and care. Starting from the awareness of the fluidity of these categories, the paper suggests that food at school be neither connected nor reduced to a dichotomous and static view. It proposes a more nuanced understanding of food practices, in which forms of productive biopower and subversive care are deeply intertwined and it discusses how children, staff and parents daily negotiate these entanglements.